BUSINESS ENVIRONMENT OF RAIL TRANSPORT IN THE CONTEXT OF THE VALUE CHAIN - Mirosław KRZEŚNIAK; Marianna JACYNA; Piotr PRYCIŃSKI; Jakub MURAWSKI; Michał BAŃKA (Scientific Journal of Silesian University of Technology. Series Transport)
The value chain can be defined as a set of all processes and procedures necessary to deliver a product or service to the end-user through various stages of development. A concept of the value chain is essential in the context of transport, as the transport process is usually one of the last elements of the value chain and determines the final value of a product or service offered. In recent years, the domestic and international rail transport market has undergone significant changes, including ongoing globalisation processes, growing importance of international trade, increase in intermodal transport significance, numerous investment outlays in transport infrastructure, means of transport, and the area of rail transport interoperability. All the above-described aspects have an impact on the value chain in transport. This paper presents an analysis of the value chain in transport processes in an aspect of rail transport. Elements of the railway transport organisation process, which affect the entire value chain, were briefly characterised in this article. Moreover, based on statistical data and a literature review, factors that fundamentally impact the efficient organisation of rail transport processes were identified.